Pusat Kebudayaan Jepang Di Pekanbaru Dengan Penerapan Prinsip Desain Kenzo Tange - Karissa, Lulu; Aldy, Pedia; S, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Culture is a comprehensive lifestyle that is complex, abstract and broad. Along with the globalization, many cultures from other countries are entering and growing in Indonesia. One of the cultures that attract and take interest of Indonesians is Japanese Culture. Japanese culture has spread all over the world including Indonesia. Lots of Indonesians are interested in applying Japanese culture with the aim to become a better person. Japanese culture has been known at every point of the city in Indonesia including Pekanbaru. Activities related to Japanese culture are often held in Pekanbaru. In order to accommodate the enthusiasm of people who want to know and learn about Japanese culture, a particular place is needed to accommodate the cultural activities. The Japanese Cultural Center building is an activity center that specifically into Japanese culture to give insight, educative, recreational and as symbol to strengthen Indonesia-Japan bilateral Relations, and as a recreational function. The design of this building will apply a theme derived from the design principles of a Japanese architect Kenzo Tange, to create Japanese atmosphere in the building. Kenzo Tange has the characteristics of modernism and keeps showing Japanese architecture in its design. Based on the function and theme of building design, came up a concept of